2008
DOI: 10.1073/pnas.0707269105
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin light chains function in mannose phosphate receptor trafficking via regulation of actin assembly

Abstract: endocytosis ͉ huntingtin-interacting protein ͉ trans-Golgi network

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
93
1
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(120 citation statements)
references
References 55 publications
24
93
1
2
Order By: Relevance
“…Thus, CLCs are dispensable for uptake of some GPCRs, as further observed in transfected cells, displaying CLCdependent internalization of DOR, but not β2AR. Our findings plus earlier observations that CLCs are required for internalization of some GPCRs (5), but not several classical CCV cargoes (3,4), suggest that CLCs are needed for endocytosis depending on the type and/or configuration of cargo present in a clathrin-coated pit. Variations in cargo crowding and local lipid organization affect membrane-bending properties, which in turn require different coat properties for deformation into a vesicle (35).…”
Section: Clc Depletion From Cell Lines Establishes Selectivity For DIsupporting
confidence: 65%
See 1 more Smart Citation
“…Thus, CLCs are dispensable for uptake of some GPCRs, as further observed in transfected cells, displaying CLCdependent internalization of DOR, but not β2AR. Our findings plus earlier observations that CLCs are required for internalization of some GPCRs (5), but not several classical CCV cargoes (3,4), suggest that CLCs are needed for endocytosis depending on the type and/or configuration of cargo present in a clathrin-coated pit. Variations in cargo crowding and local lipid organization affect membrane-bending properties, which in turn require different coat properties for deformation into a vesicle (35).…”
Section: Clc Depletion From Cell Lines Establishes Selectivity For DIsupporting
confidence: 65%
“…Vertebrates have two CLC isoforms, CLCa and CLCb, encoded by separate genes, CLTA and CLTB (1). Depletion of both isoforms from tissue culture cells by siRNA treatment showed that CLCs are not required for clathrin-mediated uptake of classic CCV cargoes, such as transferrin receptor (TfR), epidermal growth factor receptor, or low-density lipoprotein receptor (2)(3)(4). CLCs were, however, implicated in uptake of three G protein-coupled receptors (GPCRs) (5).…”
mentioning
confidence: 99%
“…2C). An increase in a number of proteins of the endomembrane system was also identified in the absence of Atg7, such as clathrin heavy chain (26), two lysosomal proteins, and Atg12, an autophagy-related protein which when conjugated to Atg5 by Atg7 forms an integral part of autophagosomal membranes (27). Most importantly, this analysis revealed that mitochondrial proteins were consistently and preferentially detected in Atg7 −/− samples only, further confirming that in the absence of autophagy, peripheral blood cells have impaired removal of mitochondria.…”
Section: Resultsmentioning
confidence: 97%
“…Proteins were separated by 10% SDS-PAGE and blotted on HyBond nitrocellulose membranes (GE Healthcare), which were blocked for 1 h in TBS-T (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 0.1% Tween 20) containing 5% nonfat dry milk. Membranes were then incubated 3 h in 1% nonfat milk with the respective antibodies: m,hLDLR (1:1000, R&D Systems), hTfR (1:1000, BD Biosciences), hPCSK9 (1:2500) (10), hCLCa and b (1:10,000) (19), hARH (1:1000, Abcam), ␤-actin (1:5000, Sigma). Appropriate horseradish peroxidase-conjugated secondary antibodies (1:10,000, Sigma) were used for detection with enhanced chemiluminescence using the ECL plus kit (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
“…chains CLCa and CLCb are not required for clathrin-mediated endocytosis but are critical for clathrin-mediated trafficking between the trans-Golgi network and the endosomal system (19). Accordingly, KD of both isoforms in HepG2 cells (KD CLCs ) resulted in the clustering of the cation-independent mannose 6-phosphate receptor, characteristic of disruption of the intracellular Golgi-lysosomal pathway (Fig.…”
Section: Disruption Of Intracellular Trafficking Increases Endogenousmentioning
confidence: 99%